1973
DOI: 10.1029/ja078i010p01487
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray electrons from 0.2 to 8 Mev: Pioneer 8 and 9 measurements of their spectrum, time variations, and interplanetary radial gradient

Abstract: Using data from the University of New Hampshire cosmic ray experiment on the Pioneer 8 and 9 space probes at radial distances from 0.75 to 1.10 AU from the sun, we have made a detailed examination of the spectrum, time variations, and interplanetary gradients of cosmic ray electrons from ~0.3 to 8 Mev. These data cover the time period from December 1967 to April 1969. Obvious solar flare electron increases have been removed from the data, so that the remaining data should represent quiet time electron behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

1974
1974
1976
1976

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
3
9
1
Order By: Relevance
“…The recently reported observations of small positive gradients for these low energy electrons by Webber et al (1973a) further supports the contention of their galactic origin. These measurements were made by comparing the electron flux measured aboard the Pioneer 8 and 9 spaceprobes with that measured simultaneously aboard Imp 4 located near the Earth.…”
Section: In~oductionsupporting
confidence: 71%
See 3 more Smart Citations
“…The recently reported observations of small positive gradients for these low energy electrons by Webber et al (1973a) further supports the contention of their galactic origin. These measurements were made by comparing the electron flux measured aboard the Pioneer 8 and 9 spaceprobes with that measured simultaneously aboard Imp 4 located near the Earth.…”
Section: In~oductionsupporting
confidence: 71%
“…The fact that the electron flux measured during quiet time increases was included as a subset of the data used to determine the low energy gradients confirms the galactic origin for these quiet time increases as well as for the quiescent electron flux (Webber et al, 1973a). The fact that the electron flux measured during quiet time increases was included as a subset of the data used to determine the low energy gradients confirms the galactic origin for these quiet time increases as well as for the quiescent electron flux (Webber et al, 1973a).…”
Section: In~oductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recently these measurements have been extended down to energies about a few tens of keV (Lin, et al, 1972;Webber, et al, 1973d;Hurford, et al, 1973a) and from the observed temporal variations, electrons above 100 keV are considered to be of galactic origin. One notices from the inset of .18), one is inclined to consider these low energy electrons to be of secondary origin; the present situation therefore doesn't warrant any new mechanism to be invoked (Ramaty, et al, 1972) to understand the observations.…”
Section: The Origin Of Cosmic Ray Electronsmentioning
confidence: 99%